Perancangan Fotografi Parodi Pada Budaya Populer Dalam Karakter Super Hero - Oky Mauludya; Sudrajat Sudrajat; Putri Sukmawati (Universitas Informatika dan Bisnis Indonesia, 2022)
The birth of modernization of life has changed the perspective and pattern of people's lives, thus enabling the emergence of a new civilization, namely the consumptive and hedonic culture of life in the midst of urban society. This phenomenon has become something that is not strange to be a subject of discussion, it has even